Outcomes of cardiopulmonary resuscitation in patients with pulmonary arterial hypertension. (1st April 2022) - Yang, Jenny Z.; Odish, Mazen F.; Mathers, Hannah; Pebley, Nicole; Wardi, Gabriel; Papamatheakis, Demosthenes G.; Poch, David S.; Kim, Nick H.; Fernandes, Timothy M.; Sell, Rebecca E.
Abstract: Over the past 20 years, despite significant advancements in pulmonary arterial hypertension (PAH) medical therapy, many patients require admission to the hospital and are at risk for in‐hospital cardiac arrest (IHCA). Prior data found poor survival in PAH patients after cardiac arrest. The purpose of this study was to explore post‐IHCA outcomes in PAH patients receiving advanced medical therapies. This is a single‐center retrospective study of PAH patients who underwent cardiopulmonary resuscitation for IHCA between July 2005 and May 2021. Patients were identified through an internal cardiac arrest database. Twenty six patients were included. Half of the cohort had idiopathic PAH, with 54% of patients on combination therapy, 27% on monotherapy, and 19% of patients on no therapy. Mean right atrial pressure, mean pulmonary artery pressure, cardiac index, and pulmonary vascular resistance were 13 ± 6 mmHg, 57 ± 13 mmHg, 2.0 ± 0.7 L/min/m 2, and 14.5 ± 7.6 Wood units, respectively. Most common etiology of cardiac arrest was circulatory collapse. Initial arrest rhythm in all but one patient was pulseless electrical activity. Six patients (23%) achieved return of spontaneous circulation (ROSC) and one patient (4%) survived to hospital discharge. Rates of ROSC and survival to discharge after IHCA are poor in patients with PAH. Even patients with mild hemodynamics had low likelihood of survival. In patients who are lung transplant candidates, there should be early consideration of extracorporeal support before cardiac arrest.